ANALISIS KEMAMPUAN PENDANAAN PEMERINTAH DAERAH DALAM RANGKA MEMBERIKAN JAMINAN KESEHATAN BAGI MASYARAKAT MISKIN - Rahayu, Sri Lestari (Badan kebijakan Fiskal, 2013)
In the year 2010 the number of citizens who have health coverage reaching 139 424 348 or 59.07 percent of Indonesia's population, while the remaining 40.93 percent do not have health insurance. Province of Nangroe Aceh Darussalam and South Sulawesi entire population already have health insurance, while that of South Sumatera and Bali respectively reached 99.60 percent and 99.56 percent. Health insurance needs to be evaluated, whether based on capitation funding awarded in accordance with the number of people, .or diverted to improving the quality of health services in health centers, hospitals, incentives for medical personnel, provision of medicines, as well as the procurement of medical equipments in accordance with the local government, so that the whole communities to utilize health care facilities specified.